Internet connectivity disruption in Uganda (Uganda) - Voidly (2026)
CRITICAL severity mixed detected in Uganda. Confidence: 65%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: UG-2026-0028
Keywords: censorship; UG; mixed; critical